2022
DOI: 10.1200/jco.22.01504
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I First-in-Human Study of ABBV-383, a B-Cell Maturation Antigen × CD3 Bispecific T-Cell Redirecting Antibody, in Patients With Relapsed/Refractory Multiple Myeloma

Abstract: PURPOSE ABBV-383, a B-cell maturation antigen × CD3 T-cell engaging bispecific antibody, has demonstrated promising results in an ongoing first-in-human phase I study (ClinicalTrials.gov identifier: NCT03933735 ) in patients with relapsed/refractory multiple myeloma (RRMM). Herein, we report safety and efficacy outcomes of this phase I dose escalation/expansion study. METHODS Patients with RRMM (≥ three prior lines including a proteasome inhibitor, an immunomodulatory drug, and an anti-CD38 monoclonal antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…The seven studies shown in Table 1 include published data on 681 participants. CRS was reported in 59%, of which 1.3% was grade 3 [ 27 , 28 , 53 , 64 , 95 , 96 , 97 ].…”
Section: Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…The seven studies shown in Table 1 include published data on 681 participants. CRS was reported in 59%, of which 1.3% was grade 3 [ 27 , 28 , 53 , 64 , 95 , 96 , 97 ].…”
Section: Safetymentioning
confidence: 99%
“…In the phase 1 study of the BCMA BsAb ABBV-383, no step-up doses or premedications were administered. CRS occurred in 72% of patients receiving 60 mg of ABBV-383 (2% grade 3–4) [ 96 ]. Another means of reducing CRS may be to incorporate additional therapies with immunomodulatory capabilities.…”
Section: Safetymentioning
confidence: 99%
“…Finally, ABBV-383 has standard availability, unlike CAR-T cell therapies, and a shorter hospitalization time than other BCMA and CAR-T cell therapies. The limitations of this study are related to the small number of patients enrolled [ 75 ]. Another ongoing phase 1/2 study (NCT03761108) involves REGN5458, which is a bispecific BCMAxCD3 antibody.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Data from a case series showing activity of CD38-targeting antibodies in pPCL, combined with improved clinical outcomes in high-risk MM with CD38 antibodies, 26 suggest that CD38 antibodies can be used as part of first-line treatment. Furthermore, because of the high efficacy of T-cell immunotherapies in extensively pretreated MM, including those with high-risk cytogenetics, [27][28][29][30][31] T-cell redirecting bispecific antibodies and chimeric antigen receptor T-cell therapies should also be evaluated in pPCL. Inclusion of patients with pPCL in trials, with early access to novel agents, should be encouraged.…”
Section: Treatment Of Ppclmentioning
confidence: 99%